Ethnographic Political Studies: Challenges and Prospects - عديلة محمد الطاهر (Milev Journal of Research and Studies, 2020)
Despite the prevalence of qualitative methods in the scientific research community interested in studying political phenomena, ethnography remains marginalized in the disciplines of political science and international relations, whether at the local or global level, so this article came to explore the state of ethnography in the field of political studies. The first part of the article dealt with introducing the ethnographic curriculum, its contents and problems, and the second part dealt with the investigation of the roots of interest in ethnography in political studies and the topics of interest and advantages that ethnography can offer, and the third part is devoted to studying the challenges faced by the use of ethnography in political research and the prospects that lie ahead.